Design of a 340 GHz phase‐velocity‐taper travelling wave tube. Issue 14 (13th June 2018) - Shao, Wei; Zhou, Qing; Tian, Hanwen; Shi, Xianbao; Wang, Zhanliang; Wei, Yanyu; Duan, Zhaoyun; Gong, Yubin; Feng, Jinjun
Abstract : Staggered double‐vane slow wave structure as the core part of the travelling wave tube (TWT) has been more popular in recent years. However, the electron efficiency of this structure is not enough high for higher frequency, especially THz. In this study, phase‐velocity‐taper method is utilised for the improvement of TWT's efficiency at 340 GHz. The reflection and transmission coefficients of the whole tube with attenuator show good propagation characteristics over the wide frequency range from 330 to 345 GHz. The particle‐in‐cell simulation results indicate that the output power can increase about 32% at 340 GHz with respect to that of the without‐taper structure. The corresponding electron efficiency is improved from 2.8 to 3.5% by phase‐velocity‐taper. However, the simulation results also show that the tube can produce over 30 W output power in the frequency range from 330 to 343 GHz with an operating voltage of 21.3 kV, a current of 0.043 A, and an input power of 10 mW. In addition, a sheet beam electron gun with a beam current of 43 mA, a beam voltage of 21.3 kV, and beam waist cross‐sectional dimension of 0.3 mm × 0.08 mm is also designed as the particle source of the sheet‐beam TWT.